Strategi Penginjilan Kontekstual dalam Konteks Teologi Poskolonial - Hutabarat, Samuel; Silalahi, Frans (Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
This article delves into strategies that the Church may pursue in implementing contextual evangelism within the framework of Postcolonial Theology. Postcolonial Theology arose during the Post-colonial era as an effort to rid the Church of Eurocentric influences. Nevertheless, this 'purification' led to more negative and radical changes. In order to carry out the mission of evangelism in alignment with God's Word and within the local context, the Church must take a clear stance on Postcolonial Theology. The qualitative research methodology employed in this study includes an in-depth study approach, a descriptive approach method, and a literature study method. The findings indicate that Postcolonial Theology can be conceptually accepted and utilized in a contextual evangelism setting, while maintaining a focus on the authentic teachings of the Bible.